Associations between cardiac arrhythmias and cardiovascular disease incidence and all-cause mortality: the Kailuan study - Xuemei Yang; Tingting Geng; Yinshun Peng; Liufu Cui; Shuohua Chen; Guodong Wang; Xiang Gao; Shouling Wu (BMC, 2024)
Abstract Aims Cardiac arrhythmia is a rising public health issue. The aim of this study was to determine the associations of atrial fibrillation (AF) and heart block with cardiovascular disease (CVD) incidence and all-cause mortality. Methods and results We included 141,362 participants (mean age [49.3], 80.9% men) from the Kailuan study. Arrhythmias were diagnosed through a 12-lead electrocardiograph (ECG). Mortality and CVD events were ascertained through multiple sources, including a municipal social insurance institution, hospital records, death certificates, and regular active follow-ups. During a median follow-up of 12.5 years, 18,301 total deaths and 13,208 cases of CVD were documented. The multivariable-adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) comparing participants with AF to those without arrhythmia were 1.76 (1.61-1.93) for all-cause mortality, 2.11 (1.86-2.39) for CVD, 3.99 (3.33-4.79) for heart failure, and 1.56 (1.30-1.90) for stroke. Further, comparing participants with heart block to those without arrhythmia, the multivariable-adjusted HRs (95% CIs) were 1.31 (1.24-1.38) for all-cause mortality, 1.26 (1.18-1.35) for CVD, 1.40 (1.23-1.59) for heart failure, and 1.25 (1.15-1.37) for stroke. Additionally, there were generally stronger associations for AF and heart block with all-cause mortality and CVD in younger participants compared with their older counterparts (Ps-interaction ≤ 0.02) and a stronger association between AF and CVD in women compared with men (Ps-interaction ≤ 0.006). Conclusion AF and heart block were associated with a higher risk of subsequent adverse CVD events and mortality. Our findings highlight the importance of strategies for preventing cardiac arrhythmias to reduce the risk of CVD and mortality.